Systematic review: YouTube recommendations and problematic content - Muhsin Yesilada; Stephan Lewandowsky (Internet Policy Review, 2022)
There has been much concern that social media, in particular YouTube, may facilitate radicalisation and polarisation of online audiences. This systematic review aimed to determine whether the YouTube recommender system facilitates pathways to problematic content such as extremist or radicalising material. The review conducted a narrative synthesis of the papers in this area. It assessed the eligibility of 1,187 studies and excluded studies using the PRISMA process for systematic reviews, leaving a final sample of 23 studies. Overall, 14 studies implicated the YouTube recommender system in facilitating problematic content pathways, seven produced mixed results, and two did not implicate the recommender system. The review's findings indicate that the YouTube recommender system could lead users to problematic content. However, due to limited access and an incomplete understanding of the YouTube recommender system, the models built by researchers might not reflect the actual mechanisms underlying the YouTube recommender system and pathways to problematic content.
Keywords: 300; YouTube; Extremism; Online radicalisation; Recommendation algorithms; Content recommender systems